2012
DOI: 10.1097/aci.0b013e328357ca53
|View full text |Cite
|
Sign up to set email alerts
|

Safety of engineered allergen-specific immunotherapy vaccines

Abstract: Purpose of review-The purpose of the review is to summarize and comment on recent developments regarding the safety of engineered immunotherapy vaccines.Recent findings-In the last 2 years, several studies were published in which allergy vaccines were developed on the basis of chemical modification of natural allergen extracts, the engineering of allergen molecules by recombinant DNA technology and synthetic peptide chemistry, allergen genes, new application routes and conjugation with immune modulatory molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…Overall, one can hypothesize that immunotherapy with mCyp c 1 will dampen Th2/IgE-skewed allergic immune responses by induction of blocking IgG/IgG 4 antibodies and of T reg /Th1-type responses [44,45]. Two alternative strategies for increasing safety and efficacy of immunotherapy under development are aiming at reducing the risk of anaphylactic side effects by either just targeting the T-cell arm (T-cell epitope peptide immunotherapy) [46] or the induction of blocking IgG antibodies (B-cell epitope peptides conjugated to immunogenic carrier proteins) [[44], and references therein].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, one can hypothesize that immunotherapy with mCyp c 1 will dampen Th2/IgE-skewed allergic immune responses by induction of blocking IgG/IgG 4 antibodies and of T reg /Th1-type responses [44,45]. Two alternative strategies for increasing safety and efficacy of immunotherapy under development are aiming at reducing the risk of anaphylactic side effects by either just targeting the T-cell arm (T-cell epitope peptide immunotherapy) [46] or the induction of blocking IgG antibodies (B-cell epitope peptides conjugated to immunogenic carrier proteins) [[44], and references therein].…”
Section: Discussionmentioning
confidence: 99%
“…Only since the availability of molecular biological and cloning techniques could epitopes involved in allergic inflammation be identified that can now be used in specific immunotherapies. Several novel therapeutic and prophylactic therapies against allergy are currently under investigation (for literature survey, see [248][249][250][251]). …”
Section: Vaccination In Allergy and Cancermentioning
confidence: 99%
“…This allows the conservation of conformational structure and T cell epitopes of the allergen, thus achieving therapeutic effect by stimulating regulatory T cells but not resulting in severe side effects as in conventional immunotherapies [38]. The use of mimotope opens a new pathway for allergy treatment by specifically targeting at B cells devoid of T cells epitopes [39].…”
Section: Figure 2: Role Of Regulatory T Cells In Immunotherapymentioning
confidence: 99%